2018
DOI: 10.1094/php-10-17-0065-rs
|View full text |Cite
|
Sign up to set email alerts
|

Apple Disease Control and Bloom-Thinning Effects by Lime Sulfur, Regalia, and JMS Stylet-Oil

Abstract: Apple (Malus × domestica Borkh.) growers require management practices that will produce high-quality fruit while minimizing the number of chemicals used for adequate disease control and horticultural practices. Certain chemicals applied for bloom thinning also have fungicidal properties and could provide protection against early season diseases in addition to crop reduction. Over 5 years, treatments of lime sulfur (LS), Regalia (an organically approved biofungicide), and JMS Stylet-Oil (JSO) were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The giant knotweed extract (Regalia; Marrone Bio Innovations, Davis, CA), an elicitor for plant defense, effectively reduced the powdery mildew disease severity and disease progress in this current study. Similar results of giant knotweed extract in reducing powdery mildew in cucumber (Cucumis sativus), tomato (Solanum lycopersicum), and apple (Malus domestica) (Baysal- Gurel and Miller, 2015;DeLong et al, 2018;Giotis et al, 2012;Herger and Klingauf, 1990;Rur et al, 2018;Zhang et al, 2016). The antifungal activity of giant knotweed extract is by activating the plant defense system, preventing the growth and germination of fungal conidia (B elanger and Benyagoub, 1997; Konstantinidou-Doltsinis et al, 2006).…”
Section: Discussionmentioning
confidence: 77%
“…The giant knotweed extract (Regalia; Marrone Bio Innovations, Davis, CA), an elicitor for plant defense, effectively reduced the powdery mildew disease severity and disease progress in this current study. Similar results of giant knotweed extract in reducing powdery mildew in cucumber (Cucumis sativus), tomato (Solanum lycopersicum), and apple (Malus domestica) (Baysal- Gurel and Miller, 2015;DeLong et al, 2018;Giotis et al, 2012;Herger and Klingauf, 1990;Rur et al, 2018;Zhang et al, 2016). The antifungal activity of giant knotweed extract is by activating the plant defense system, preventing the growth and germination of fungal conidia (B elanger and Benyagoub, 1997; Konstantinidou-Doltsinis et al, 2006).…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, lime sulphur can serve as a source of sulphur nutrition and is also known as a post‐infection fungicide against various fungal diseases (Holb et al, 2003; Jamar et al, 2008). Additionally, it has an excellent disinfectant activity on disease inoculum present on fallen leaves (Cromwell et al, 2011; DeLong et al, 2018), which can be a valuable option if there is no possibility to collect and compost fallen leaves. Nevertheless, it needs to be noted that the use of lime sulphur raises significant environmental concerns and current regulations are advised to restrict the use of lime sulphur in apple orchards.…”
Section: Discussionmentioning
confidence: 99%
“…Lime sulfur (calcium polysulfide), another plant disease control reagent, has been allowed to be used in organic crop production as an insecticide (including acaricide or mite control) by the USDA National Organic Program (NOP). Previous studies showed that lime sulfur could control pear scab and rust ( 20 ) and apple scab and cedar apple rust ( 21 ). However, whether these fumigants and fungicides can be adapted to American ginseng and effectively mediate root rot disease and replant problems is still unknown.…”
Section: Introductionmentioning
confidence: 99%